PENERAPAN SELF ASSESSTMENT SYSTEM DALAM MENINGKATKAN KESADARAN ATAS KEPATUHAN MEMBAYAR PAJAK DIKABUPATEN GOWA - Masrullah Masrullah; Asriati Asriati; Nur Reski Alfiah S (Jurnal Riset Perpajakan: Amnesty, 2021)
This type of research is a qualitative descriptive study. Where the research is carried out in the field and the survey is directly in the place to be studied. The results of the research on the realization of tax reporting using the Self Assessment System at the Gowa Regency Revenue Agency in 2018, the tax revenue was IDR 11,056,558,000 out of 326 total tax receipts registered with the SPT. And so, in 2019 the tax revenue was IDR 13,870,577,200 out of the 181 total tax revenues registered in the SPT. Therefore, the percentage of tax compliance achieved by the Regional Revenue Agency of Gowa Regency in 2018-2019 was 49.16%.